Pengaturan Aplikasi Pupuk Nitrogen Untuk Meningkatkan Toleransi dan Pemulihan Tanaman Padi Terhadap Cekaman Terendam - Gribaldi Gribaldi; Rujito A. Suwignyo; Merry Hasmeda; Renih Hayati (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2013)
The influence of global climate to the Indonesian climate condition has been in serious condition which was already in high intensity. Flood becomes the fenomena in almost all area in Indonesia. In a swamp area, it can obstruct rice plant cultivation. The submerged rice plant create the obstruction of the rice plant photosynthesis and stress after being submerged. So that  an effort is needed to increase  its tolerance and recovery in order the reduction of the unhulled crop can be reduced.   This study was aimed to obtain a method to increase rice stage is vegetative  tolerance and recovery to submergence stress through the arrangement of nitrogen fertilizer aplication and rice variety.  The experimental design used was factorial completely randomized design with six replications. The factor consists of rice varieties (Inpara 3, Inpara 5, IR 64) and  treatment (P): P1: no submergence, all N dosage prior planting; P2: submerged (7-14 DAP), all N dosage prior planting; P3: submerged (7-14 DAP), all N dosage prior planting + (Si+Zn); P4: submerged (7-14 DAP), ½ N dosage prior planting + ½ N dosage 42 DAP + (Si+Zn); P5: submerged (7-14 DAP and 28-35 DAP), all N dosage prior planting; P6: submerged (7-14 DAP and 28-35 DAP), all N dosage prior planting + (Si+Zn); P7:  submerged (7-14 DAP and 28-35 DAP), ½ N dosage prior planting + ½ N dosage 42 DAP + (Si+Zn). The results showed that the arrangement of nitrogen fertilizer application before submerged to rice plant can increase the rice plant tolerance and recovery to the submerged stress.  The increasing of tolerance and recovery can be obtained at the rice variety given ½ N dosage prior planting + ½ N dosage 42 DAP + (Si+Zn).